NoSQL database design processes: a comparative study - Marrero, Luciano (2023)
NoSQL databases have emerged as a response to scalability problems presented by relational databases when used in Big Data contexts. These databases do not have a standard process for designing data schemas, but have emerged as solutions directly at the physical level. As NoSQL databases have gained popularity, different NoSQL design processes and/or methodologies have been proposed, which are necessary to understand the semantics of the stored data. This paper presents a comparative study of NoSQL database design processes.